Seismic safety assessment of symmetric and asymmetric buildings for different performance levels - Nagasai, T.; Kamatchi, P. (Journal of Structural Engineering, 2024)
In this paper, a methodology for assessment of seismic safety in terms of margin ratios and conditional exceedance probabilities has been demonstrated for a symmetric and an asymmetric building for different performance levels viz. Immediate Occupancy (IO), Damage Control (DC), Life Safety (LS) and Collapse Prevention (CP) in line with the procedure suggested in Federal Emergency Management Agency (FEMA) P695. Ground motions used in incremental dynamic analysis are chosen from Pacific Earthquake Engineering Research Next Generation Attenuation Models (PEER NGA) database, consistent with 2475 years mean return period spectra for the Bhuj site, India. Fragility curves are developed for different performance levels and margin ratios are estimated for symmetric and asymmetric building and comparisons are made with the respective acceptance criteria. Variations in margin ratios and conditional probabilities, if the building is assumed to be situated at different zones and different soil types have also been brought out for the chosen symmetric and asymmetric building. Exceedance probabilities are found to be higher for asymmetrical building compared to symmetrical building for IO, DC, LS performance levels and exceedance probabilities are higher for symmetrical building for CP performance level. Similarly, the margin ratios for symmetrical building are higher for IO, DC, LS performance levels and margin ratio for asymmetrical building is higher for CP performance level. This study indicates the necessity for inclusion of the effect of asymmetry in seismic safety assessment and also the need for estimation of exceedance probabilities and margin ratios for different performance levels.